2004
DOI: 10.1007/s00704-004-0074-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variations in leaf area index and light extinction in a Fagus sylvatica stand as estimated from global radiation profiles

Abstract: The paper presents a model that estimates leaf area index (LAI) from above- and below-canopy global radiation measurements. The approach is based on a detailed description of radiation regime above and below the canopy. One EuroFlux site, a beech forest ( Fagus sylvatica L.) at Hesse, France was selected for model testing. The time-courses of daily LAI from 1996 to 2001 were simulated by the model. Since the simulated LAI curves include some random daily variations due to the quality of global radiation measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Several considerations increase our confidence in the in situ LAI measurements. Our approach is simple, well established [ Fuchs et al , 1984; Pierce and Running , 1988; Welles and Cohen , 1996], and especially well suited for determining the relative LAI changes over a year [ Breda , 2003; Wang et al , 2004]. Sensitivity analyses confirmed that the seasonal cycle of LAI was not a result of our primary assumptions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Several considerations increase our confidence in the in situ LAI measurements. Our approach is simple, well established [ Fuchs et al , 1984; Pierce and Running , 1988; Welles and Cohen , 1996], and especially well suited for determining the relative LAI changes over a year [ Breda , 2003; Wang et al , 2004]. Sensitivity analyses confirmed that the seasonal cycle of LAI was not a result of our primary assumptions.…”
Section: Discussionmentioning
confidence: 77%
“…However, litterfall remained low during December (Figure 5), and we found no evidence, either direct or anecdotal, of an increase in leaf abscission at km‐83 during this period. Previous studies have also noted discrepancies between the seasonal patterns of in situ measured and MODIS‐derived LAI [ Wang et al , 2004; Cohen et al , 2006].…”
Section: Discussionmentioning
confidence: 99%
“…However, manual measurement employing these methods provides only sporadic data. Continuous monitoring of radiative transmittance (R t D S b /S 0 ) is often used to determine the temporal variation in LAI (Maass et al, 1995;Holst et al, 2004;Wang et al, 2004). We thus produced continuous LAI data from the continuous monitoring of R t and periodic LAI data derived from litter-fall collection data.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Transmittance of incident radiation through the canopy is often used to monitor temporal variation in LAI (Maass et al, 1995;Holst et al, 2004, Wang et al, 2004. Based on the BeerLambert equation, radiative transmittance (R t = S b /S 0 ), which exponentially decreases with increasing LAI, is estimated as an index of LAI.…”
Section: Determination Of Canopy Duration and Transpiration Periodmentioning
confidence: 99%